Charged probes: turn-on selective fluorescence for RNA. Issue 2 (16th November 2017) - Shirinfar, Bahareh; Seema, Humaira; Ahmed, Nisar
Abstract : Imidazolium-based charged fluorescent probes for the selective in vitro and in vivo recognition of RNA over other biomolecules. Abstract : RNA controls many biological processes. The selective detection and imaging of RNA molecules can provide information about their location, kinetics, and functions at the cellular level. The imidazolium-based positively charged probes would play a significant role in the deep investigation of RNA biomolecules to check their therapeutic potential and aid in the future rational molecular and drug design.